2022
DOI: 10.1007/s00262-022-03350-x
|View full text |Cite
|
Sign up to set email alerts
|

The common HLA class I-restricted tumor-infiltrating T cell response in HPV16-induced cancer

Abstract: Immunotherapies targeting truly tumor-specific targets focus on the expansion and activation of T cells against neoantigens or oncogenic viruses. One target is the human papilloma virus type 16 (HPV16), responsible for several anogenital cancers and oropharyngeal carcinomas. Spontaneous and vaccine-induced HPV-specific T cells have been associated with better clinical outcome. However, the epitopes and restriction elements to which these T cells respond remained elusive. To identify CD8+ T cell epitopes in cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Previous studies using available prediction algorithms have identified a number of HLA class I‐restricted HPV16 E6 peptides. Of these, only a few are HLA‐A*02:01‐restricted and have been clinically validated, most notably the E6 29‐38 epitope 10,33 . Nevertheless, an E6‐reactive TCR specific to the E6 29‐38 epitope that was tested in a phase I clinical trial showed only two partial responses out of 12 treated patients 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using available prediction algorithms have identified a number of HLA class I‐restricted HPV16 E6 peptides. Of these, only a few are HLA‐A*02:01‐restricted and have been clinically validated, most notably the E6 29‐38 epitope 10,33 . Nevertheless, an E6‐reactive TCR specific to the E6 29‐38 epitope that was tested in a phase I clinical trial showed only two partial responses out of 12 treated patients 11 .…”
Section: Resultsmentioning
confidence: 99%
“…9 Later, a TCR reactive to the E6 29-38 peptide was identified from tumor infiltrating lymphocytes (TILs) of a cancer patient and tested in a phase I/II clinical trial, 10 albeit with limited success, with just two out of twelve patients showing partial responses. 11 No further clinical trials have been reported to date with the E6 [29][30][31][32][33][34][35][36][37][38] TCR. More recently, however, deep sequencing studies have identified several E6 variants in patients with high-grade squamous intraepithelial lesions (HSIL) caused by HPV16, with a hotspot located at codon 32.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, relatively little work has been performed regarding HPV-specific TILs in HPV+ HNSCC. Prior works showed the presence of intratumoral HPV E6- and E7-specific CD4+ and CD8+ T cells, which predominantly secreted IFN-γ but also a substantial amount of IL-17, suggesting the intratumoral presence of HPV-specific T H 1 and T H 17 responses in HPV+ HNSCC ( Figure 1 ) [ 83 , 131 , 132 ]. However, additional information about the phenotypic and transcriptional landscape of HPV-specific TILs required to assess the differentiation state of these cells and their potential responsiveness to various treatment modalities has been lacking.…”
Section: Hpv-specific Immune Responses In Hpv+ Hnsccmentioning
confidence: 96%
“…Open access that are critical components of antigen recognition and are influential in the outcome of viral infections. 14 15 Historically, numerous studies have focused on HPV16 E proteins E6 and E7 as targets of T-cell reactivity 16 and immunotherapy due to the established role of E6 and E7 in neoplastic transformation. [17][18][19][20][21][22][23] Despite limited early clinical successes targeting these antigens, durable complete tumor regression has been an elusive goal.…”
Section: What This Study Addsmentioning
confidence: 99%
“…One epitope predicted to have high affinity in HPV16 E7-amino acids 11-19, was not predicted to be presented in HPV33 (online supplemental figure 2E). HPV16 E7 [11][12][13][14][15][16][17][18][19] has been reported to be a critical epitope in HPV16 recognition and has been the target of several Open trials seeking to treat HPV16-driven malignancies. 21 43 44 Therefore, we infer that a deficiency in HPV E7 recognition by T cells in HPV33 HLA-A*02:01+ may pose an elevated risk of virally-driven malignancy for this HPV genotype.…”
Section: Open Accessmentioning
confidence: 99%